Dermoscopic Diagnosis of a Non-Pigmented Skin Tumor: Eccrine Poroma - Aksoy, Hasan; Cebeci Kahraman, Filiz; Aslan Kayıran, Melek; Erdemir, Vefa Aslı; Gürel, Mehmet Salih; Çobanoğlu Şimşek, Bengü (European Journal of Therapeutics, 2023)
Dear Editor, Eccrine poroma stands as a benign adnexal neoplasm that originates from the acrosyringium. It typically emerges as solitary, flesh-colored, or erythematous papules, plaques, or nodules, primarily appearing in areas with sweat glands. As well as pigmented lesions, dermoscopy has proven to enhance the clinical diagnosis of numerous non-pigmented skin tumors, including eccrine poroma. Herein we present a case of eccrine poroma located on the dorsal aspect of the left foot, with characteristic dermoscopic features. A 60-year-old woman was admitted with an asymptomatic lesion on the dorsum of her left foot, which had manifested approximately four years before. Clinically, the lesion presented as a well-circumscribed, violaceous, 0.9x0.9 cm papule (Figure 1a). Dermoscopic examination revealed flower-like and leaf-like vascular patterns, white interlacing areas, glomerular vessels, and milky red globules (Figures 1c-d). The lesion was excised and histopathologic findings were consistent with eccrine poroma (Figure 1b). Eccrine poroma (EP) is an adnexal tumor originating in the intraepidermal part of the eccrine sweat gland duct. Dermoscopy and histopathology help to differentiate EP from pyogenic granuloma, seborrheic keratosis, verruca vulgaris, basal cell carcinoma, squamous cell carcinoma, and amelanotic melanoma. Well-defined dermoscopic features in EP are: White interlacing areas around vessels, milky-red globules, flower-like and leaf-like vascular patterns, glomerular vessels, hairpin vessels, yellow structureless areas, poorly visualized vessels, and well-circumscribed globular or lacuna-like structures separated by white to pink mesh bands [1-3]. Histologically, EP manifests as a well-contained tumor constituted of proliferative cuboidal or poroid cells, often extending from the basal epidermis into the dermal layer. Shave, electrosurgical destruction or simple excision may be the treatment of lesions, depending on the depth of the lesion. Kind Regards